Penerapan Teknologi Smart Farming untuk Pertanian Peternakan Zero Waste pada Lahan Kering - I Gede Adnyana; I Putu Arya Mulyawan; Bagus Kusuma Wijaya; Ida Bagus Putu Mardana; Ketut Srie marhaeni Julyasih; I Nengah Suarmanayasa (Universitas Perjuangan Tasikmalaya, 2026)
Bonyoh Village in Bangli Regency has great potential for development in the sectors of horticultural agriculture, livestock, educational agro-tourism, and renewable energy. Located on the southern slopes of the Mount Batur Caldera at an altitude of 850–950 meters above sea level, the village has a cool climate and high rainfall that support the cultivation of high-value crops such as Siam oranges, Arabica coffee, and chili peppers. However, this potential has not been fully utilized due to limited basic infrastructure, particularly the lack of a permanent irrigation system and proper water management. The hilly topography prevents the village from receiving water supply from Lake Batur, making agricultural productivity highly dependent on rainfall. In the livestock sector, work efficiency remains low since feeding and waste management activities are still performed manually. To address these issues, a technology demonstration plot approach, hands-on training, and institutional mentoring are implemented. Appropriate technological innovations include the construction of a well-dam system with a submersible pump, the application of smart farming through solar-powered drip irrigation for citrus cultivation, and the utilization of livestock waste for biogas production. This program is expected to improve energy efficiency, enhance agricultural productivity, and realize a sustainable, zero-waste integrated farming system.